Educational Migration of Applicants Among Regions of the Russian Federation as a Data Source for Planning the Higher Education System Development - A. V. Dozhdikov; E. V. Kornilova (Высшее образование в России, 2023)
The scientific problem of the study is related to the identification of educational migration for university admission against the background of youth migration. The practical problems of the study are focused on the creation of analytical conditions for decision-making and planning for the education system development: the distribution of enrollment targets, financing and resource supporting the infrastructure development, and the development of the human resources potential of Russian universities. The object of the study is interregional youth educational migration for university admission. Federal universities data is described as the object of present study. Sources: official state statistics data of 2017-2021, “big data” is the results of passing the Unified State Examinations (USE) and the choice of university and direction of study by students for 2020. The research methodology is connected with the analysis of official statistics, the Russian regions typology according to the characteristics of youth migration: recipient regions, donor regions, regions of a mixed or “transit” type (leaving graduates are replaced by newcomers), closed (low intensity of migration processes). Educational migration was identified by analyzing and comparing databases on the results of the USE and the results of university admission. Stable patterns of migration processes, migration trends and directions have been identified as a result of the study.